The Tuina Acupressure Boosts Toddler Weight: Akupresur Tuina Meningkatkan Berat Badan - sekarlita Normaulida Anggraini; Evi Rinata (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of tuina acupressure on the weight of malnourished toddlers in Jenisgelaran Village, Bareng, Jombang, Indonesia. Using a quasi-experimental design, 22 toddlers were divided into control and treatment groups, with the latter receiving daily tuina acupressure for 15 minutes over one month. Weight changes were measured before and after the intervention. Results showed a significant increase in the weight of toddlers who received tuina acupressure (P = 0.003). These findings suggest that tuina acupressure can effectively enhance weight gain in malnourished toddlers, recommending its integration into health practices by caregivers and healthcare providers. Highlights: 1. Effective Intervention: Tuina acupressure increased toddler weight significantly (P = 0.003).2. Study Methodology: Quasi-experimental design with pretest-posttest on 22 toddlers.3. Practical Application: Recommends tuina acupressure for malnutrition management in toddlers. Keywords: tuina acupressure, toddler weight gain, malnutrition, quasi-experimental study, Indonesia